2005
DOI: 10.1007/s00417-005-0110-8
|View full text |Cite
|
Sign up to set email alerts
|

First experiences with high-density silicone oil (Densiron) as an intraocular tamponade in complex retinal detachment

Abstract: The anatomical success rate without further interventions of 45.8% (22 of 48 patients) seems unsatisfactory. However, in evaluating the potential of Densiron, it should be considered that all patients in this study had previous surgery with standard procedures, including silicone oil, which had already failed. Intraoperative laser photocoagulation of the periphery of the upper quadrants might reduce the risk of retinal re-detachments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
97
5
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(112 citation statements)
references
References 33 publications
3
97
5
7
Order By: Relevance
“…A few studies have reported on the use of 'Heavy Silicone Oil' for RD. [11][12][13][14] Indications for the use of heavy oil includes PVR, RD with inferior breaks and inability to posture. Variable anatomical results have been reported using Densiron with up to 81% reattachment rates with single surgery in one series 11 and 46% reattachment in another, 12 although the latter study recruited only complex PVR cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A few studies have reported on the use of 'Heavy Silicone Oil' for RD. [11][12][13][14] Indications for the use of heavy oil includes PVR, RD with inferior breaks and inability to posture. Variable anatomical results have been reported using Densiron with up to 81% reattachment rates with single surgery in one series 11 and 46% reattachment in another, 12 although the latter study recruited only complex PVR cases.…”
Section: Discussionmentioning
confidence: 99%
“…13 In some series, heavy oil emulsification has been reported to be low, with little or no clinical impact. 11,13,14 However, Sandner and Engelmann 12 reported emulsification of Densiron in seven out of 48 patients with pseudo-hypopyon formation in four patients. For this reason, they routinely performed anterior chamber irrigation upon Densiron removal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 Following the relative disappointment with these early heavy tamponades, we now seem to have entered a phase in which we might see the introduction of these vitreous substitutes into routine clinical use. Three recently developed heavy tamponades, Oxane HD, Densiron 68 and HWS 46-3000, have demonstrated better results and fewer complications compared to the earlier used substances, [20][21][22] and are now slowly gaining acceptance within the vitreoretinal community, [23][24][25][26][27] despite notable scepticism. In this article, the previous and current heavy tamponades, their indications, and the associated complications are reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown good anatomical and visual outcomes with no emulsification upto 3 months with these agents. [28][29][30] HSO works well as a long-term tamponade agent for complex retinal detachments involving inferior proliferative vitreoretinopathy. 31 …”
Section: Heavy Silicone Oilmentioning
confidence: 99%